National Debt Capacity of the Mindanao Economy: A Cointegration Analysis - Juevesano, Jesus (International Journal of Economics and Financial Issues, 2025)
This paper aims to determine the debt-bearing capacity of Mindanao’s regional economies in relation to the national debt from 2000 to 2024. Obtaining the Gross Regional Domestic Product (GRDP) data sourced from the Philippine Statistics Authority and national debt figures from the Department of Finance, the study computes economic capacity as a function of GRDP-to-debt ratios. Employing the Johansen Cointegration Test, which identifies long-run equilibrium relationships among the six Mindanao regions shows that while Mindanao’s aggregate economic capacity increased significantly, averaging 33% of the national total, regional differences continue. Northern Mindanao and SOCCSKSARGEN exhibit strong capacity and rapid adjustments to disequilibrium, serving as economic stabilizers. While BARMM and Caraga display slower adjustment, reflecting structural constraints. The cointegration analysis reveals that shocks or growth in one region significantly influence others, reinforcing the interdependence of Mindanao’s regional economies. To achieve sustained national debt management and inclusive growth requires regionally integrated policy interventions, investment in infrastructure, and equitable fiscal strategies. A Mindanao-wide development framework, rather than region-specific planning, is essential to maximize the island’s collective capacity and contribution to national wealth.